2016
DOI: 10.1172/jci87430
|View full text |Cite
|
Sign up to set email alerts
|

From the gut to the strut: where inflammation reigns, bone abstains

Abstract: C o m m e n t a r y2 0 4A new player in sex steroid deficiency-related bone lossOsteoporosis is a leading cause of morbidity in the increasing population of aging adults. In postmenopausal women, fracture incidence far exceeds the combined incidence of breast cancer, stroke, and myocardial infarction. Bone loss arises from accelerated resorption by osteoclasts, which outpaces the accompanying increase in bone formation by osteoblasts (1). Postmenopausal osteoporosis has traditionally been solely attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The immune system plays a critical role in mediating GM-related effects on the regulation of bone mass. Cytokines and chemokines such as TNF-α, CCL-2, IL-10, SERT (Serotonin Transporter) and Tph1 may be possible mediators between the GM and steroid deficiency-induced osteoporosis [ 41 , 42 ]. Therefore, further mechanistic studies, including fecal microbiota transplantation, are needed to verify the causality of gut microbiota on steroid deficiency-induced osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system plays a critical role in mediating GM-related effects on the regulation of bone mass. Cytokines and chemokines such as TNF-α, CCL-2, IL-10, SERT (Serotonin Transporter) and Tph1 may be possible mediators between the GM and steroid deficiency-induced osteoporosis [ 41 , 42 ]. Therefore, further mechanistic studies, including fecal microbiota transplantation, are needed to verify the causality of gut microbiota on steroid deficiency-induced osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that LPS administration prior to injury elevates Tlr5/7/8 transcription in the joint [ 10 , 21 ]. TNF-α promotes osteoclastogenesis by increasing RANK-L expression in bone marrow cells and therefore elevating the number of osteoclast precursor cells [ 20 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other pathogenic processes associated with endothelial dysfunction might negatively impact bone in T2D. For example, increased inflammation, cellular adhesion, and oxidative stress might also contribute to the changes in bone structural and material properties that occur in T2D. Impaired bone endothelial function is just one potential mechanism by which T2D results in bone fragility.…”
Section: Discussionmentioning
confidence: 99%